PERBANDINGAN METODE PEMBUATAN EKSTRAK TERPURIFIKASI BEE PROPOLIS DARI LEBAH MADU (Apis mellifera) BERDASARKAN KADAR FLAVONOID TOTAL DIHITUNG SEBAGAI RUTIN - Suwijiyo Pramono; Agustina Dian Puspitasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
Propolis is a complex mixture of beeswax, sugar, and gum trees collection of honeybees (Apis mellifera). One of the compounds that have a pharmacological effect is flavonoid. Flavonoid can be obtained in large concentration and high purity with purified extraction method. The extraction was done with 96% ethanol, followed by purification with 30% ethanol, chloroform, ethyl acetate (in Method I), or followed with hot water and ethyl acetate (in Method II). The content of flavonoids detected by Thin Layer Chromatography, the stationary phase, silica gel 60F 254, the mobile phase n-butanol- acetic acid- water (3: 1: 1 % v/v ). The total flavonoid concentration was measured by UV-Vis spectrophotometer based on Zou method, calculated as routine. Results were analyzed by paired sample t-test. The mean level of total flavonoids from propolis extract before purification was 1.23 ± 0.3698 %w / w. Purification of ethanolic extract of 96% propolis with Method I and II, resulting in a total flavonoid concentration of 9.97 ± 1.5656 (8.1 times) and 11.78 ± 1.2965% w / w (9.6 times). Paired samples t-test with SPSS 16 showed the effectiveness of purification with significance value 0.048.